Composition and Association of a Semi-natural Forest Created on Barren Land - Tripathi, K. P.; Singh, Bajrang (Indian Forester, 2006)
A semi-natural forest developed on sodic wasteland during the last 40 years at Banthra Research Station of National Botanical Research Institute, Lucknow, was characterized as mixed dry subtropical forest with deciduous and evergreen species. The forest constituted about 74 species belonging to 35 families. These were classified in overstory (44), understory (19), ground layer (8) and climber (3). Several species of overstory were also found in understory and ground layer vegetation, which indicated the regeneration potential of a few species. In overstory vegetation Syzygium cumini, Bauhinia variegata, in understory Leucaena leucocephala, Barleria prionitis and in ground layer Clerodendrum vescosum had greatest abundance. The forest constituted about 30 m2 ha-1 basal area predominantly occupied by overstory trees. Three stands (S1, S2, S3) were selected on the basis of gross morphology. In S1 stand Bauhinia variegata and Albizia lebbek were most dominant species on the basis on IVI (41) and basal area (4.35 m2 ha-1), Leucaena leucocephala was the dominant species of understory on the basis of IVI (98). Barleria prionitis and Leucus biflora were dominating in ground layer with basal cover 1.94 and 0.7 m2 ha-1, and IVI 44, and 84. In S2 stand, Bauhinia variegata dominated with greatest IVI (65) in overstory vegetation, whereas Syzygium heyneanum had greatest basal area (6.6 m2 ha-1) with 64 IVI and it was also dominated in understory vegetation with maximum IVI (51). Barleria prionitis (IVI 124, basal cover 113.4 m2 ha-1) and Clerodendrum vescosum (IVI 74, basal cover 108.4 m2 ha-1) were dominated in ground layer vegetation. In S3 stand Syzygium heyneanum were dominated in overstory and understory vegetation on the basis of IVI (60 and 51), but Albizia lebbek had greatest basal area (6.4 m2 ha-1) in overstory. Syzygium heyneanum also dominated in understory vegetation while Pedilanthus tithymaloides was most common in ground layer vegetation. Syzygium heyneanum had greatest population density (159 plant/ha) for overstory and 524 plant/ha for understory vegetation while in ground layer vegetation Clerodendrum vescosum was the most abundant species with 780 plants/ha.